TRICHODERMA HARZIANUM AND PSEUDOMONAS SP. MEDIATED MANAGEMENT OF SCLEROTIUM ROLFSII ROT IN TOMATO (LYCOPERSICON ESCULENTUM MILL.) - S. P. SINGH; H. B. SINGH; D. K. SINGH (The Bioscan, 2013)
Trichoderma spp. and Pseudomonas spp. are known for their biocontrol potential and growth promotion activity. Combination of these two microbes was used to assess the synergistic effect of compatible isolates for plant growth promotion and management of S. rolfsii. Trichoderma harzianum and Pseudomonas and their combination were applied as seed and seedlings treatment in tomato. Consortium treatment showed the greater plant growth promotion activity in comparison to solo treatment. Consortium treatment showed highest chlorophyll content (1.05mgg-1 fresh weight of leaves) while in the pathogen inoculated control lowest amount was recorded (0.8mgg-1 fresh weight of leaves). The lowest mean disease rating (MDR) 1.96 and maximum percent disease reduction (PDR), 53.23% recorded in consortium treatment. The yield was also significantly higher in bioagents treated treatments, T3 (37.41 tons h-1), T4 (36.60 tons h-1), T5 (43.84 tons h-1) and untreated unchallenged treatment (45.29 tons h-1) than untreated challenged control (24.07 tons h-1). From these results it can be concluded that the application of consortium of compatible bioagents will enhance the plant growth and biological control of phytopathogens in contrast to treatment with single bioagent.